2015
DOI: 10.1002/alr.21690
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative development of the sinus control test: a survey evaluating sinus symptom control

Abstract: The SCT is a simple, patient generated questionnaire that can measure the control of CRS without requirement of endoscopy or CT evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 18 publications
1
53
0
1
Order By: Relevance
“…The notion of CRS control remains somewhat more nebulous. Multiple different studies have sought to develop a definition of CRS control . Some of these studies have suggested utilising objective measures of disease, such as endoscopic findings, to define CRS control, while others have suggested using patient history, such as utilisation of CRS‐related corticosteroids, to define CRS control .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The notion of CRS control remains somewhat more nebulous. Multiple different studies have sought to develop a definition of CRS control . Some of these studies have suggested utilising objective measures of disease, such as endoscopic findings, to define CRS control, while others have suggested using patient history, such as utilisation of CRS‐related corticosteroids, to define CRS control .…”
Section: Discussionmentioning
confidence: 99%
“…14,17 Because sinonasal symptomatology is the dominant contributor to decreased QOL in CRS, 14 Multiple different studies have sought to develop a definition of CRS control. 1,21,22 Some of these studies have suggested utilising objective measures of disease, such as endoscopic findings, to define CRS control, 21 while others have suggested using patient history, such as utilisation of CRS-related corticosteroids, to define CRS control. 22 However, in all of these different proposed definitions of CRS control, patient-reported CRS control is consistently advocated to assess CRS control.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors found that attendance at clinic at the later time points (ie, 12 and 24 months) was predicted by asthma, higher computed tomography (CT) score, prior sinus surgery, and recalcitrant subtypes such as aspirin-exacerbated respiratory disease, allergic fungal sinusitis, nasal polyposis, and granulomatosis with polyangiitis. To aid in quantifying follow-up measures for CRS patients, Banglawala et al 12 developed the 4-item Sinus Control Test (SCT), which includes questions on nasal obstruction, nasal discharge, sinus symptom interference with tasks at work or home, and recent treatment with antibiotics or steroids in the previous 2 weeks. This new instrument was evaluated vs rhinologist assessment of disease control, with a resulting Cohen's kappa of 0.68.…”
mentioning
confidence: 99%